Founders of the future : the science and industry of Spanish modernization - Useche, Óscar Iván (Campos Ibéricos: Bucknell Studies in Iberian Literatures and Cultures Ser., 2022)
"In this ambitious new interdisciplinary study, Useche proposes the metaphor of the social foundry to parse how industrialization informed and shaped cultural and national discourses in late nineteenth- and early twentieth-century Spain. Across a variety of texts, Spanish writers, scientists, educators, and politicians appropriated the new economies of industrial production-particularly its emphasis on the human capacity to transform reality through energy and work-to produce new conceptual frameworks that changed their vision of the future. These influences soon appeared in plans to enhance the nation's productivity, justify systems of class stratification and labor exploitation, or suggest state organizational improvements. This fresh look at canonical writers such as Emilia Pardo Bazán, Concha Espina, Benito Pérez Galdós, Vicente Blasco Ibáñez, and José Echegaray as well as lesser known authors offers close readings of their work as it reflected the complexity of Spain's process of modernization"--